2018
DOI: 10.3201/eid2406.171587
|View full text |Cite
|
Sign up to set email alerts
|

Frequent Implication of Multistress-TolerantCampylobacter jejuniin Human Infections

Abstract: Campylobacter jejuni, a major cause of bacterial foodborne illnesses, is considered highly susceptible to environmental stresses. In this study, we extensively investigated the stress tolerance of 121 clinical strains of C. jejuni against 5 stress conditions (aerobic stress, disinfectant exposure, freeze-thaw, heat treatment, and osmotic stress) that this pathogenic bacterium might encounter during foodborne transmission to humans. In contrast to our current perception about high stress sensitivity of C. jejun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 23 publications
3
32
0
Order By: Relevance
“…The low temperature (4°C) employed in the current study was intentionally chosen to enhance the potential to detect differences in survival among different strains of C. jejuni and C. coli shed by the birds in the feces. Campylobacter strains can differ in their cold tolerance (41)(42)(43)(44), and such differences may contribute to the current findings. In addition to temperature, other attributes, including the avian source (chicken versus turkey) and the Campylobacter species and strains involved, may contribute to the observed differences in survival between our study and others.…”
Section: Discussionmentioning
confidence: 80%
“…The low temperature (4°C) employed in the current study was intentionally chosen to enhance the potential to detect differences in survival among different strains of C. jejuni and C. coli shed by the birds in the feces. Campylobacter strains can differ in their cold tolerance (41)(42)(43)(44), and such differences may contribute to the current findings. In addition to temperature, other attributes, including the avian source (chicken versus turkey) and the Campylobacter species and strains involved, may contribute to the observed differences in survival between our study and others.…”
Section: Discussionmentioning
confidence: 80%
“…Campylobacter jejuni is a zoonotic pathogen, and it is a major cause of foodborne diseases all over the world (Ica et al, 2012). Planktonic C. jejuni is extremely susceptible to multiple stressors (Lee et al, 2019;Oh et al, 2019), especially to oxygen pressure in the environment, as aerotolerance factors heavily in the transmission of C. jejuni to humans via foods under aerobic conditions (Euna et al, 2015;Oh et al, 2018). C. jejuni can be observed in a viable but non-culturable (VBNC) state in vitro (Magajna and Schraft, 2015;Stetsenko et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that the formation of C. jejuni monoculture biofilms is difficult (Joshua et al, 2006;Hanning et al, 2008). The current study simulated the conditions (Oh et al, 2018) involved in the C. jejuni infection of humans (at 37 • C under aerobic conditions representing the natural atmosphere) and explored the mechanisms related to infection.…”
Section: Introductionmentioning
confidence: 99%
“…In cases involving human infections, there is a high prevalence of aerotolerant Campylobacter strains. One recent study found that out of 121 sample strains, 65 were considered hyper-tolerant and 46 were tolerant to oxygen [70]. Strains hyper-tolerant to oxygen also exhibited tolerance to other stressors.…”
Section: Emerging Challengesmentioning
confidence: 99%
“…Strains hyper-tolerant to oxygen also exhibited tolerance to other stressors. Of the 65 strains hyper-tolerant to oxygen, 56 were tolerant to heat treatment at 72 • C for 30 s [70]. Because Campylobacter has been associated with high environmental sensitivity, the survivability of C. jejuni has been underestimated, which may suggest increased monitoring of this pathogen may be necessary [70].…”
Section: Emerging Challengesmentioning
confidence: 99%